Volunteering Among Adults Aged 50+ and their Motivations for Volunteering: The Case of Europe - Ferhan Saniye Palaz (Journal of Economy Culture and Society)
For older adults, volunteering has the capacity to increase social inclusion and well-being. Even though volunteering trends in this group have been studied, knowledge of their motivations for volunteering is scarce. This article investigates the socio-demographic determinants of older adults’ participation in volunteering and their motivation for doing so. Usingmicrodata from the Survey of Health, Aging, and Retirement in Europe, we evaluate the relationship between socio-demographic characteristics and volunteering and its motivations using chi-square tests, CochranArmitage trend test, and quadratic regression analysis. We investigated individuals aged 50+ in 11 countries (n = 26931). The results show that 12.5% of the sample does volunteer work, and the frequency of volunteering initially increases by age and then decreases. Volunteering is more common among men, partnered individuals, and those whose perceived health and economic status are good. Differences are visible between countries, which could be partially explained by their welfare regime. The most frequent motivations for volunteering observed by us are as follows: 1) to contribute something useful, 2) to meet other people, 3) enjoyment of the volunteer activity, and 4) feeling needed as a volunteer.